SUMBANGAN INDUSTRI KERAJINAN DULANG KAYU TERHADAP PENDAPATAN TOTAL RUMAH TANGGA PETANI - Ni Luh Putu Erma Mertaningrum (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
Dulang is one of the means that used as offerings at Hinduism ceremony in Bali. One of the villages in Bali that produces dulang woodcraft is Pengotan Village. In the midst of technological developments, the existence of a home industry of dulang woodcrafts is one of the media in preserving local culture. The purpose of this study is to find out how much acceptance of farmer household is; and to find out how big the contribution of dulang industry to total household income of farmers. Data analysis method that used in this study is the formula of acceptance, the labor productivity and costs productivity and the percentage contribution of the craft. The results showed that, the handicraft industry is able to provide additional income to the total income of the household, and dulang woodcraft workmanship able to providing a substansial contribution to earning total farm households.